Sometimes less is more: inhibitory infrared light during early reperfusion calms hyperactive mitochondria and suppresses reperfusion injury. (31st October 2022) - Morse, Paul T.; Wan, Junmei; Bell, Jamie; Lee, Icksoo; Goebel, Dennis J.; Malek, Moh H.; Sanderson, Thomas H.; Hüttemann, Maik
Abstract : Ischemic stroke affects over 77 million people annually around the globe. Due to the blockage of a blood vessel caused by a stroke, brain tissue becomes ischemic. While prompt restoration of blood flow is necessary to save brain tissue, it also causes reperfusion injury. Mitochondria play a crucial role in early ischemia-reperfusion injury due to the generation of reactive oxygen species (ROS). During ischemia, mitochondria sense energy depletion and futilely attempt to up-regulate energy production. When reperfusion occurs, mitochondria become hyperactive and produce large amounts of ROS which damages neuronal tissue. This ROS burst damages mitochondria and the cell, which results in an eventual decrease in mitochondrial activity and pushes the fate of the cell toward death. This review covers the relationship between the mitochondrial membrane potential (ΔΨm ) and ROS production. We also discuss physiological mechanisms that couple mitochondrial energy production to cellular energy demand, focusing on serine 47 dephosphorylation of cytochrome c (Cyt c ) in the brain during ischemia, which contributes to ischemia-reperfusion injury. Finally, we discuss the use of near infrared light (IRL) to treat stroke. IRL can both stimulate or inhibit mitochondrial activity depending on the wavelength. We emphasize that the use of the correct wavelength is crucial for outcome: inhibitory IRL, applied early during reperfusion, can prevent the ROS burst from occurring, thus preserving neurological tissue.